Roman Empire. An Investigation on the Effectiveness of Flood Risk Prevention Systems in the Roman Period. Research Carried Out between August and October 2022 - Trivelloni, Ilaria (e-Forschungsberichte des DAI, 2023)
The present paper aims to investigate prevention systems to avoid the effects of disastrous events and subsequent reconstruction methods of urban and suburban spaces following catastrophic events such as flooding. Archaeological evidence and textual sources reveal the attention and awareness in ancient Roman society for these unpredictable events. For this purpose, some cities, whose planning has been greatly affected by the presence of particularly overflowing watercourses, are taken as case studies. The idea is to promote an investigation into the efficacy or ineffectiveness of those systems, encouraging a discussion of what is still happening today.